Optimum sustainable utilisation of the whole fruit of Jatropha curcas: An energy, water and food nexus approach - Mohammad Alherbawi (14155767) (2021)
The growing anthropogenic greenhouse gas (GHG) emissions combined with the rise of the demand on energy resources has expedited research into sustainable alternatives to fossil fuel. In this context, biomass has increased in popularity and acquired a significant share of the global energy mix in a relatively short time. However, several biomass resources have triggered wide criticism for compromising food resources, agricultural lands and fresh water to produce energy crops. Therefore, a second generation of non-edible biomass such as Jatropha curcas has become a major biofuel feedstock for several countries. Not only can its oil be converted into liquid fuels, but also the Jatropha fruit residues have high calorific value and are processed into several forms of energy. Several studies have investigated the different processing technologies to produce energy and food-related products, although no conclusions have been made on the most sustainable pathway for Jatropha utilisation considering its interlinkages to the energy, water and food resources, whilst considering its possible contributions to mitigating carbon emissions and the development of circular economies. As such, this study investigates 11 processing pathways for the major three components of Jatropha fruit from cradle to gate via a combination of three key tools including Energy-Water-Food (EWF) Nexus, Global Warming Potential (GWP) and Return on Investment (ROI). Aspen Plus software is used to simulate the production processes including transesterification, hydrotreatment, hydrocracking, gasification, pyrolysis, hydrothermal liquefaction, anaerobic digestion, saccharification and fermentation, incineration and detoxification. In addition, a mathematical model is developed to run a five-objective optimisation study using MATLAB. The model identifies an opportunity to process the Jatropha oil by transesterification (49%), hydrotreatment (28%) and hydrocracking (23%). while it is suggested that the seedcake is best utilised directly as fertilisers (35%) and processed for energy production by pyrolysis (30%) and anaerobic digestion (17%). Nevertheless, the shells of Jatropha are best utilised via SSF (32%), pyrolysis (28%), anaerobic digestion (22%) and incineration (11%). Other Information Published in: Renewable and Sustainable Energy Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rser.2020.110605